(untitled) (Italiano LinguaDue, 2014)
La letteratura ha una funzione etica cui non può rinunciare. Il letterato, la figura più importante su un territorio, ha il compito di leggere la realtà, di interpretarla, di comunicarla. È il faro che si deve accendere e guidare le azioni degli uomini: un popolo che rinuncia ai suoi letterati e all’etica della letteratura, è un popolo che si perde. Così egli canta la Negritudine, la storia e il dolore della sua gente; e la sua poesia, con un forte impegno civile, si propone di dar voce a chi non ce l’ha. The poet and his times Literature has an undeniable ethical function. The writer, the most important figure in a place, has the task of reading, interpreting and communicating reality. Literature is the beacon that one turns to and that guides the actions of people. A country that renounces its writers and the ethics of literature is a lost nation. Thus the writer sings of Negritude, the history and the pain of his people. Her poetry, with strong social commitment, aims to give voice to those who do not have one.